Service level agreements: governance in outsourcing facility management - Mohamed, Armai (Penerbit UTM Press, 2015)
Governance mechanism is playing vital role in service performance. Service level agreement is a governance mechanism to facilitate the performance management of the facility management services outsourced. Service level agreement is indispensable document to be referred to ensure that the facility management services delivery comply the quality standard stipulated in the agreement. The service level agreement elements represent the required service performance. Previous research indicates that one of the reasons for the agreement failure is due to unclear and confusing service level agreement elements. The aim of this study is to develop the service level agreement fundamental elements for facilities management services in outsourcing contract.